Produtividade, ciclagem de nutrientes e eficiência emergética em função da diversidade vegetal em sistemas agrícolas e caatinga conservada - Aguiar, Maria Ivanilda de (2012)
Nutrient cycling and energy transformation processes fuel plant productivity and are directly related to ecosystem diversity. The preservation of diversity has thus been identified as a way to improve the sustainability of agroecosystems. It also follows that agroforestry systems (AFS) are recommended since they maintain high plant diversity, increase carbon and nutrient stocks and promote emergy efficiency. Agroforestry systems represent an alternative to traditional agricultural systems, which are responsible for large losses of diversity and environmental degradation in Brazil’s semiarid northeast. It is assumed that the greater plant diversity in AFS yields greater productivity, improves soil nutrient inputs, and increases carbon and nutrient stocks as well as energy efficiency. We evaluated a model agroforestry production system consisting of three areas: agrosilvopastoral, silvopastoral and preserved caatinga vegetation (CAT). Also, data was taken from a traditional management system including an area under cropping and two areas under fallow for six and nine years. The objectives of this work were to assess whether AFS remain similar to preserved vegetation and whether fallow periods restore land to its initial condition, in terms of: (i) the species composition and community structure of herbaceous and tree/shrub strata; (ii) plant diversity and biomass production; (iii) carbon and nutrient stocks in standing vegetation, litter and the soil and (iv) emergy flux transformations. We found that species composition and plant productivity were similar in the AFS and preserved caatinga, however in AFS the structure of the plant community was modified and diversity indices were reduced. Soil carbon and nutrient stocks in AFS were similar to those in CAT, but stocks in standing biomass and litter were lower. Overall, the AFS performed better in terms of emergy, due to more efficient energy use, a lesser environmental impact and greater renewability. The fallow periods following traditional cropping allowed the species composition, productivity and carbon and nutrient stocks in soil and litter to recover. However, areas under fallow differed from CAT in terms of tree community structure, with a greater number of individuals and species. Tree species found in fallow areas reach smaller sizes than under CAT. Therefore total biomass and carbon and nutrient stocks were lesser under fallow than CAT. Agroforestry systems managed in an integrated fashion represent great potential for sustainability, since they provide agricultural, pastoral and wood products while maintaining vegetation structure characteristics which allow constant fluxes of energy and nutrient cycling, as occurs under preserved vegetation.